ANALYSIS OF THE CAMEL METHOD FOR ASSESSING THE FINANCIAL HEALTH CONDITION OF PT. BANK NEGARA INDONESIA (PERSERO) TBK, DURING THE COVID-19 PANDEMIC - Dwibin Kannapadang (SEAN Institute, 2023)
This study aims to determine the condition of health finance at PT. Bank Negara Indonesia Tbk during a pandemic in 2019–2020 using the CAMEL method. The type of research used is quantitative descriptive, where the author will describe and calculate the financial performance analysis at PT Bank Negara Indonesia Tbk from 2019–2020. As for the technique analysis used in the study, that is the CAMEL ratio by multiplying the credit value of each ratio with the CAMEL weight, which is standardized by Bank Indonesia (BI). The results of this study show a final CAMEL score of 95.1 for 2019 and 85.9 for 2020. All of these results are in the range of 81–100 with a healthy predicate. Thus, it can be concluded that the financial performance of PT. Bank Negara Indonesia Tbk (Persero), which is listed on the Indonesia Stock Exchange using the CAMEL method from 2019 to 2020, is healthy.